Molecular Interaction and Evolution of Jasmonate Signaling With Transport and Detoxification of Heavy Metals and Metalloids in Plants - Chen, Xuan; Jiang, Wei; Tong, Tao; Chen, Guang; Zeng, Fanrong; Jang, Sunghoon; Gao, Wei; Li, Zhen; Mak, Michelle; Deng, Fenglin; Chen, Zhong-Hua (Frontiers in Plant Science, 2021)
An increase in environmental pollution resulting from toxic heavy metals and metalloids (e.g. cadmium, arsenic, and lead) causes serious health risks to humans and animals. Mitigation strategies need to be developed to reduce the accumulation of the toxic elements in plant-derived foods. Natural and genetically-engineered plants with hyper-tolerant and hyper-accumulating capacity of toxic minerals are valuable for phytoremediation. However, the molecular mechanisms of detoxification and accumulation in plants have only been demonstrated in very few plant species such as Arabidopsis and rice. Here, we review the physiological and molecular aspects of jasmonic acid and the jasmonate derivatives (JAs) in response to toxic heavy metals and metalloids. Jasmonates have been identified in, limiting the accumulation and enhancing the tolerance to the toxic elements, by coordinating the ion transport system, the activity of antioxidant enzymes, and the chelating capacity in plants. We also propose the potential involvement of Ca2+ signaling in the stress-induced production of jasmonates. Comparative transcriptomics analyses using the public datasets reveal the key gene families involved in the JA-responsive routes. Furthermore, we show that JAs may function as a fundamental phytohormone that protects plants from heavy metals and metalloids as demonstrated by the evolutionary conservation and diversity of these gene families in a large number of species of the major green plant lineages. Using ATP-Binding Cassette G (ABCG) transporter subfamily of six representative green plant species, we propose that JA transporters in Subgroup 4 of ABCGs may also have roles in heavy metal detoxification. Our paper may provide guidance towards the selection and development of suitable plant and crop species that are tolerant to toxic heavy metals and metalloids.